Computer systems software support for foreign languages teaching - Kis, Yaroslav; Sloboda, Kateryna (Видавництво Національного університету «Львівська політехніка», 2009)
In this article the peculiarities of foreign languages teaching computer systems software are considered. The main types of programs are distinguished The tasks of such kinds of programs are analyzed The main objectives of these programs are pointed out.
Keywords: computer systems; language teaching; software for language teaching; databank